2005
DOI: 10.1042/cs20040352
|View full text |Cite
|
Sign up to set email alerts
|

Opposite changes in carotid versus aortic stiffness during healthy human pregnancy

Abstract: Systemic arterial compliance has been known to increase during healthy pregnancy, whereas, recently, the carotid artery has been reported to stiffen. To clarify this controversy, we simultaneously measured aortic PWV (pulse wave velocity) and carotid artery elastic parameters in a cohort of pregnant women. Twelve normotensive pregnant women were studied longitudinally during the three trimesters of pregnancy (T1, T2 and T3 respectively) and 12 weeks PP (postpartum). Carotid artery diastolic diameter and pulsat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
40
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 29 publications
8
40
1
1
Order By: Relevance
“…Pregnant women demonstrate 100-fold higher blood levels of both estrone and estradiol, and 1,000-fold higher blood level of estriol compared with non-pregnant women in the same age group. 17 These high levels of estrogen derived from the placenta may be related to decreased arterial stiffness; a few clinical studies demonstrating improved endothelial function 18 and decreased PWV during pregnancy 19,20 support this.…”
Section: Discussionmentioning
confidence: 78%
“…Pregnant women demonstrate 100-fold higher blood levels of both estrone and estradiol, and 1,000-fold higher blood level of estriol compared with non-pregnant women in the same age group. 17 These high levels of estrogen derived from the placenta may be related to decreased arterial stiffness; a few clinical studies demonstrating improved endothelial function 18 and decreased PWV during pregnancy 19,20 support this.…”
Section: Discussionmentioning
confidence: 78%
“…As part of this adaptation, muscular (brachial) artery stiffness, as measured by carotid-radial pulse wave velocity (PWV), is decreased with pregnancy (28,39). In contrast to the peripheral vasculature, the carotid artery has been found to stiffen during pregnancy (30). Several studies have indicated that some of these pregnancy-induced adaptations persist past one year after delivery (7,11).…”
mentioning
confidence: 99%
“…With aging and hypertension, rigidity of these vessels increases with a concomitant increase of diameter (Farasat 2008, Giumelly 1999, Safar 2005. In vivo elasticity is frequently measured in form of pulse wave velocity (Huotari 2010, Westerhof 2007), aortic compliance (Long 2004, Mersich 2005, input impedance (Mazzaro 2005) or augmentation index (Safar 2005). Exercise training can stimulate elastin production and reduce high-stress stiffness (DeAndrade 2010).…”
Section: Windkessel Artery and Distributing Artery Biomechanicsmentioning
confidence: 99%
“…Modern ultrasonography (from the surface of the body and also intravascular) provides sufficient means for larger vessels (Berczi 2005, Molnar 2006, Mersich 2005, Shimazu 1986). A certain level of manipulation of pressure and smooth muscle tone is possible even in human volunteers (See Fig.…”
Section: Parameters Measuring Elasticitymentioning
confidence: 99%
See 1 more Smart Citation